Practicum activities at the brackishwater aquaculture center. - Nicdao, Hermogenes O. (College of Fisheries, University of the Philippines, 1978)
In any technical institution, education would be incomplete without the application of theories in actual practice. The educational institution should make men and women fully equipped with both theoretical and practical knowledge in their chosen field of specialization. For this reason, the UP College of fisheries requires a graduating student to undergo practice-in-Industry training or practicum. The theories in the classrooms are applied in the field. But application of such theories needs skill and skill can be acquired only after some time when scores or trials and errors have calloused what used to be an innocent individual. The student who has undergone practicum activities is not yet expected to know everything that has to be known. This report covers only what we have understood and absorbed in our practicum activities. Topics that seemed vague to us were only mentioned in passing---for can anyone expect us to be skilled aquaculturists after one month of training?